OPTIMALISASI PENERAPAN TEKNOLOGI INFORMASI PADA SMART DEFENSE GUNA MENDUKUNG TUGAS POKOK TNI AL DALAM RANGKA MELAKSANAKAN FUNGSI PERTAHANAN ASPEK LAUT DI IBU KOTA NEGARA - Permana Silitonga; Eko Arie Kurniawan; Hari Wiwit W (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
Information technology is the most important element of an organization that needs to be and continues to be developed as an effort to increase professionalism to produce a world-class military capable of overcoming problems or responding to challenges and threats in the modern era. The National Capital City (IKN) is in North Penajam Paser Regency, East Kalimantan. Geographically the location is bordered by two countries, namely Malaysia and the Philippines. In addition, on the west side of the island of Borneo is bordered by the territory of Singapore and the South China Sea. The South China Sea conflict which borders the western region of Kalimantan Island will also have a defense and security impact on IKN. Lack of strength in defense and security technology in the Sea Region, he application of Defense, Security, Law Enforcement and Safety at Sea in facing the relocation of the National Capital is a crucial issue that must be faced together. The lack of defense and security forces in the sea area is also the basis for a solution to this problem.